Pendekatan Komunikasi dalam Pembinaan Mualaf di Yayasan Bina Mualaf Al Muhajirin Bumi Asri Medan - Alphy Shahri Maulana; Ari Oldwin Sitorus; Arif Indra Hasan; Azmiar Nasution; Rizqi Ramadhani Siregar (Al-Fikru, 2022)
This study aims to analyze the profile of the Bina Mualaf Al Muhajirin Bumi Asri Foundation in Medan, the communication approach in fostering converts to Islam, and financing the development of converts to converts. This research uses qualitative research methods based on descriptive studies. The informants of this research are the managers, coaches, and converts themselves. Primary data sources from research informants, and secondary sources from various documents such as foundation policy documents, and research results in the form of books and journals to support research theories. Collecting data by means of observation, interviews, and documentation studies. While the data analysis with the stages of data collection, data reduction, and drawing conclusions. The results of the study explain that the Al-Muhajirin Bumi Asri Medan Muslim converts foundation was founded on the basis of concern for converts, especially in the city of Medan. This idea was initiated by the congregation of the mosque in the Bumi Asri complex with Islamic missions. The development of converts to Islam is through a communication approach, namely subject communication, object communication, emotional communication and explicit communication. Funding for converts is free, the available funds come from donations and congregational sponsors.